An unexpected cause of hyponatremia in a cancer patient: Trimethoprim-sulfamethoxazole - Dilsa Mizrak; Emra Asfuroglu Kalkan; Ali Alkan; Halis Yerlikaya; Elif Berna Koksoy; Ebru Karci; Gungor Utkan; Ahmet Demirkazik (Journal of Oncological Sciences, 2016)
Background: Hyponatremia is one of the most common electrolyte abnormalities seen in hospitalized patients. In cancer patients, it's generally related to syndrome of inappropriate ADH secretion (SIADH). Case Report: Here, we report a breast cancer patient with hyponatremia related to high dose trimethoprim-sulfamethoxazole use for pneumonitis cariini pneumonia. Conclusion: It is important to be aware that all hyponatremias are not related to SIADH in cancer patients. For proper treatment strategies, a proper differential diagnosis is needed.